3‐Phase 4‐wire matrix converter‐based voltage sag/swell generator to test low‐voltage ride through in wind energy conversion systems. Issue 12 (1st December 2014) - Díaz, Matías; Cárdenas, Roberto; Rojas, Félix; Clare, Jon
Abstract : The high penetration of energy from wind energy conversion systems (WECSs) can have a significant influence on the stability, power quality and reliability of power systems. Therefore several countries have developed stringent grid codes in recent years in order to enhance the overall stability of power systems. In these grid codes, the capacity to fulfil low‐voltage ride through (LVRT) requirements is considered an important issue for the control of WECSs. Therefore in this study, a novel voltage sag/swell generator (VSG) based on a 4‐leg matrix converter is presented. This VSG can be used to generate the symmetrical and asymmetrical faults required to test LVRT algorithms in a laboratory environment. The performance of the VSG is experimentally demonstrated and compared with the operation of other VSGs conventionally used for LVRT studies.